2022
DOI: 10.1002/pcn5.26
|View full text |Cite
|
Sign up to set email alerts
|

Approaches and hurdles of implementing pharmacogenetic testing in the psychiatric clinic

Abstract: Pharmacogenetic (PGx) testing has emerged as a tool for predicting a person's ability to process and react to drugs. Despite the growing evidence‐base, enthusiasm, and successful efforts to implement PGx testing in psychiatry, a consensus on how best to implement PGx testing into practice has not been established and numerous hurdles to widespread adoption remain to be overcome. In this article, we summarize the most used approaches and commonly encountered hurdles when implementing PGx testing into routine ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…60 As of yet, clinical adoption of the technology in Canada and across the globe remains limited due to uncertainties about clinical utility and relevance of test findings to individuals, among other barriers. 58,60,61 Research examining the effectiveness of pharmacogenomics testing, in particular for guiding the treatment of depression, is emerging; however, to date, the findings remain mixed, with studies indicating both significant improvements and no difference in clinical outcomes compared with usual care. 57,58,62 A qualitative study reported that people in Canada with lived experiences and health care professionals are hopeful about the technology but are also awaiting more robust clinical and economic evidence.…”
Section: Pharmacogenomics Tests For Mental Health Conditionsmentioning
confidence: 99%
“…60 As of yet, clinical adoption of the technology in Canada and across the globe remains limited due to uncertainties about clinical utility and relevance of test findings to individuals, among other barriers. 58,60,61 Research examining the effectiveness of pharmacogenomics testing, in particular for guiding the treatment of depression, is emerging; however, to date, the findings remain mixed, with studies indicating both significant improvements and no difference in clinical outcomes compared with usual care. 57,58,62 A qualitative study reported that people in Canada with lived experiences and health care professionals are hopeful about the technology but are also awaiting more robust clinical and economic evidence.…”
Section: Pharmacogenomics Tests For Mental Health Conditionsmentioning
confidence: 99%
“…67, 68, and 69, just to cite a few) with the aim of implementing strategies to overcome them. 70 Indeed, a general lack of support for such testing in psychiatry has been highlighted because of the absence of standardized clinical protocols, regulations, and easy-to use workflows to guide psychiatrists, uncertainty concerning cost-effectiveness that varies significantly among countries, the entire cost of testing paid by patients with no reimbursement by health care systems, and uncertainty about regulatory policies concerning the management of PGx data with consequent ethical and legal drawbacks. Moreover, uncertainty about the clinical efficacy and generalizability of PGx testing has spread, as many studies have been conducted on relatively small samples and have been not adequately controlled for significant confounding factors.…”
Section: Important Limitations and Challenges To Be Acknowledgedmentioning
confidence: 99%
“…Therefore, further research is warranted to replicate findings in much larger data sets with the necessary statistical power, accounting for confounding factors such as placebo effects, adherence to treatments, concurrent medications, clinical symptoms, and population stratification 67 . In addition, most of the largest studies published to date have been sponsored by commercial laboratories and have used commercial combinatorial tests, raising concerns about conflict of interest, transparency, and, once again, generalizability of evidence 70 …”
Section: Important Limitations and Challenges To Be Acknowledgedmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacogenomics (PGx) (i.e. the study and use of an individual's genomic information to predict response to medications) is one such strategy that has gained significant momentum and is fueling the precision psychiatry movement (Maruf & Bousman, 2022).…”
Section: Introductionmentioning
confidence: 99%